Physics and Literature Concepts - Transfer - Aestheticization - Heydenreich, Aura; Mecke, Klaus (Literatur- und Naturwissenschaften, 2021)
Physics and Literature is a unique collaboration between physicists and literary scholars, the first book to explore together the relations between both fields in depth. Contributors analyze central aspects of literary and scientific thought and representation, and the forms of exchange between them. They clarify how narrative, fiction, metaphor and language interact with models, experiment, measurement and mathematics, across eras and genres.